On the motion of linked spheres in a Stokes flow - Box, F; Han, E; Tipton, C; Mullin, T (Springer Berlin Heidelberg, 2017)
The results of an experimental investigation into the motion of linked spheres at low Reynolds number are presented. Small permanent magnets were embedded in the spheres and torques were generated by application of an external magnetic field. Pairs of neutrally buoyant spheres, connected by either glass rods or thin elastic struts, move in a reciprocal orbit when driven by an oscillatory field. An array of three spheres linked by elastic struts buckles in a periodic, non-reciprocal manner. The induced magneto-elastic buckling propels the elemental swimmer and we find that the geometrical asymmetry of the device, introduced by the struts of different lengths, determines the swimming direction